2017
DOI: 10.1186/s12881-017-0462-z
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system gene polymorphisms and high blood pressure in Lithuanian children and adolescents

Abstract: BackgroundEpidemiological studies have demonstrated the influence of environmental factors on HBP in the population of Lithuanian children, although the role of genetic factors in hypertension has not yet been studied. The aim of this study was to assess the distribution of AGTR1, AGT, and ACE genotypes in the Lithuanian child population and to determine whether these genotypes have an impact on HBP in childhood.MethodsThis cross-sectional study enrolled 709 participants aged 12–15 years. The subjects were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
0
14
1
4
Order By: Relevance
“…In multiple binary logistic regression analyses (adjusted for age and BMI) and by categorising sleep duration into four groups (≤8 h, 8.1-8.9 h, 9.0-9.9 h, ≥10 h), shorter sleep duration was also shown to be a risk factor for increased BP. There are several studies examining the relationship between increased BP and various environmental conditions, other than sleep duration ( 22 , 23 , 24 , 25 , 26 ). In this present study, the only other significant environmental risk factor identified was location of the school the children or adolescents were attending and this was only true of the girls.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple binary logistic regression analyses (adjusted for age and BMI) and by categorising sleep duration into four groups (≤8 h, 8.1-8.9 h, 9.0-9.9 h, ≥10 h), shorter sleep duration was also shown to be a risk factor for increased BP. There are several studies examining the relationship between increased BP and various environmental conditions, other than sleep duration ( 22 , 23 , 24 , 25 , 26 ). In this present study, the only other significant environmental risk factor identified was location of the school the children or adolescents were attending and this was only true of the girls.…”
Section: Discussionmentioning
confidence: 99%
“…We selected two polymorphisms in the AGT gene, i.e., rs699 (M235T in exon 2) and rs5050 (A-20C in the promoter region), for detection. The selection of the two functional polymorphisms was based on a thorough evaluation of polymorphisms associated with vasculopathy [22, 2527]. Genomic DNA was extracted from all KD cases and controls blood using the TIANamp Blood DNA Kit (Qiagen, Dusseldorf, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…В недавно проведенном генетическом исследовании 700 литовских детей и подростков S. Simonyte и соавт. доказано влияние полиморфизма I/D гена ACE на формирование АГ у мальчиков -наличие генотипов DD и ID увеличивало риск развития АГ в 2,05 и 1,82 раза в отличие от девочек, у которых подобная ассоциация отсутствовала [26]. В выполненном нами исследовании у мужчин с АГ и носительством генотипа DD АСЕ (I/D) отмечались также более частые ранние ССЗ среди родственников по отцовской линии в сравнении с материнской линией.…”
Section: -96unclassified